EFEKTIVITAS LINDUNG NILAI BERDASARKAN PSAK 55 - Dewa Putra Krishna Mahardika (Media Riset Akuntansi, Auditing & Informasi, 2020)
The aim of this research is to measure gold-hedging effectiveness using gold futures traded in Jakarta Futures Echange. This quantitative research uses four methods in measuring hedge effectiveness: ratio analysis, regression analysis, volatility risk reduction and percentage offset ratio. The result shows that each method can give contradictory conclusion. Of the four method used to measure effectiveness only ratio analysis and percentage offset ratio that categorized gold futures as effective. Absent of compulsory single method in PSAK 55 and inconsistency result among methods allow hedger to choose the most favourable method in calculating hedging effectiveness.